Pseudouridine synthases are proviral factors for Sindbis virus in insect and mammalian cells - Nicole Stark; Ram Podicheti; Lauren Garcia; Adela Krenz; Douglas B. Rusch; Irene L. G. Newton; Richard W. Hardy (mBio, 2025)
ABSTRACT Alphaviruses are positive-sense, single-stranded RNA (+ssRNA) viruses transmitted by arthropod vectors to vertebrate hosts. Pseudouridine is the most prevalent RNA modification in the prototype alphavirus, Sindbis virus (SINV) genome, but the location, function, and the cellular machinery that deposits pseudouridine are not known. Here, we demonstrate that the host pseudouridine synthase, Nop60B, plays a proviral role in SINV replication in Drosophila melanogaster. We show that SINV infection alters the expression of Nop60B isoforms and that SINV RNA levels significantly correlate with Nop60B RNA levels in infected flies. Furthermore, ectopic expression of Nop60B in cell culture increased SINV infectivity and intracellular RNA levels, which is dependent on the catalytic function of Nop60B. We found that this proviral function is conserved as the human ortholog, dyskerin, increases SINV replication. Using Psi-seq, we mapped putative pseudouridine sites within SINV RNA. Most of the putative psi sites identified were in the structural protein coding region, and we identified a stretch of putative pseudouridine residues surrounded by sequences complementary to a snoRNA known to guide Nop60B to its RNA target. A silent mutation at one of these sites led to a reduction in SINV replication, indicating a potential functional role. Overall, our findings suggest that pseudouridine and the pseudouridine synthases contribute to alphavirus replication, adding to our broader understanding of viral replication mechanisms.IMPORTANCEAlphaviruses pose a threat to over half of the global population, and currently, there are no approved antivirals targeting alphaviruses. We identified a conserved pseudouridine synthase that is proviral for Sindbis virus (SINV) infection in insects and humans. Using Psi-seq, we identified putative pseudouridine residues in SINV RNA. Mutagenesis of putative psi sites led to a slight reduction in replication and suggests that pseudouridine residues in SINV RNA are functionally important in replication.